Molecular methods in Public Health - Metodi Molecolari in Sanità Pubblica (Italian Journal of Public Health, 2005)
Public Health (PH) practitioners are becoming increasingly interested in biomolecular techniques, this stands as testimony to the number of courses and dedicated sessions in national conferences that have occurred since 1990 which have involved several colleagues.On behalf of the past-president of Italian Society of PH (SItI), Prof.G. Renga, the volume Molecular methods in Public Health - Metodi Molecolari in Sanità Pubblica represents the first attempt to rigorously collect different contributions from Italian researchers working in the field of molecular biology as applied to PH. The volume, edited by Prof. G. Giammanco and Prof. S. De Flora and published by Centro Scientifico Editore 2004, addresses all of the traditional aspects of molecular biology in PH. It is divided into six sections, focusing on the areas of epidemiology and prevention of infectious diseases in community and nosocomial settings, the epidemiology of chronic-degenerative diseases, hygiene in the working and living environment, food and water hygiene, and genetically modified organisms (GMOs). As far as the prevention of infectious diseases is concerned, the molecular approach has shown that genotyping aetiological agents permits the comparison of different isolates collected during epidemic events, thus providing the timely reconstruction of the chain of transmission of the disease. In this context all of the recent molecular techniques used for bacteria and viral genotyping are discussed, for example, Restriction Fragment Length Polymorphisms (RFLP) of genomic DNA, Southern blotting analysis, Pulsed Field Gel Electrophoresis (PFGE), Amplified Fragment Length Polymorphisms (AFLP),ribotyping,and others based on Polymerase Chain Reaction (RAPD, ERIC-PCR, REP-PCR) and genome sequencing